Analisis Sistem Antrean Untuk Optimasi Layanan Pada Kedai Minuman Populer XYZ Di Jatinangor - Kurniawan, Koko Iwan Agus; Hasyim, Raihana Whidyani; Firdaus, Ajeng Salsabila; Ihsan, Diartanan Alghifari (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Queue management in popular beverage shops often encounters challenges, particularly in densely populated areas like Jatinangor. This study aims to: (1) analyze customer arrival patterns and service time distribution, (2) evaluate queue performance using the M/M/1 queuing model, and (3) provide strategic recommendations to enhance service quality. A quantitative descriptive approach was employed through direct observation during peak hours at XYZ Beverage Shop in Jatinangor. This study investigated data on arrival times, service durations, and queue lengths. The results revealed that customer arrivals follow a Poisson distribution with an average arrival rate (λ) of 15 customers/hour. Service times were normally distributed with an average of 2.3 minutes/customer (μ = 26 customers/hour). Queue performance based on the M/M/1 model indicated a system utilization rate (ρ) of 36.43%, an average number of customers in queue (Lq) of 0.21, and an average waiting time in queue (Wq) of 0.84 minutes. The current system is considered efficient, with a relatively short waiting time. However, it may encounter capacity issues during customer surges. Strategic recommendations include adopting a multi-server queue model (M/M/c) or implementing a digital queuing system to manage peak-hour demand. The findings also validate the applicability of classical queuing models in small-to-medium-scale F&B businesses with specific customer characteristics, such as student populations